Gut microbiota depletion by chronic antibiotic treatment alters the sleep/wake architecture and sleep EEG power spectra in mice - Ogawa, Yukino (Sci Rep, 2020)
Dysbiosis of the gut microbiota affects physiological processes, including brain functions, by altering the intestinal metabolism. Here we examined the effects of the gut microbiota on sleep/wake regulation. C57BL/6 male mice were treated with broad-spectrum antibiotics for 4 weeks to deplete their gut microbiota. Metabolome profiling of cecal contents in antibiotic-induced microbiota-depleted (AIMD) and control mice showed significant variations in the metabolism of amino acids and vitamins related to neurotransmission, including depletion of serotonin and vitamin B6, in the AIMD mice. Sleep analysis based on electroencephalogram and electromyogram recordings revealed that AIMD mice spent significantly less time in non-rapid eye movement sleep (NREMS) during the light phase while spending more time in NREMS and rapid eye movement sleep (REMS) during the dark phase. The number of REMS episodes seen in AIMD mice increased during both light and dark phases, and this was accompanied by frequent transitions from NREMS to REMS. In addition, the theta power density during REMS was lower in AIMD mice during the light phase compared with that in the controls. Consequently, the gut microbiota is suggested to affect the sleep/wake architecture by altering the intestinal balance of neurotransmitters.